Construction project safety - Schaufelberger, John, 1942-; Lin, Ken-Yu, 1975- (Hoboken, New Jersey : Wiley, 2014)
'This introduction to construction safety for construction management personnel takes a project-based approach to present potential hazards in construction and their mitigation or prevention. After introducing Accident Prevention Programs and OSHA compliance requirements, the book integrates safety instruction into the building process by following a building project from site construction through interior finish. Reinforcing this applied approach are photographs, drawings, contract documentation, and an online 3D BIM model to help visualize the onsite scenarios'--
Introduction -- Worker Compensation and Injured Worker Management -- Accident Prevention Program -- OSHA Compliance -- Safety for Project Start-up -- Safety for Site Preparation, Earthwork, and Foundation -- Safety for the Superstructure -- Safety for the Exterior Enclosure -- Safety for the Interior Construction -- Safety for the Miscellaneous Work Items.
Includes index.
Keywords: United States. -- Occupational Safety and Health Administration; Building -- Safety measures; Construction industry -- United States -- Safety measures; Construction industry -- Health aspects -- United States; Construction industry -- Safety regulations -- United States